Exacerbation frequency and clinical outcomes in adult patients with cystic fibrosis. Issue 8 (15th June 2011) - de Boer, Kaïssa; Vandemheen, Katherine L; Tullis, Elizabeth; Doucette, Steve; Fergusson, Dean; Freitag, Andreas; Paterson, Nigel; Jackson, Mary; Lougheed, M Diane; Kumar, Vijay; Aaron, Shawn D
Abstract : Background: Despite advances in treatment of cystic fibrosis (CF), pulmonary exacerbations remain common. The aim of this study was to determine if frequent pulmonary exacerbations are associated with greater declines in lung function, or an accelerated time to death or lung transplantation in adults with CF. Methods: A 3-year prospective cohort study was conducted on 446 adult patients with CF from Ontario, Canada who could spontaneously produce sputum. Patients enrolled from 2005 to 2008 and were stratified into groups based upon their exacerbation rates over the 3 year study: <1 exacerbation/year (n=140), 1–2 exacerbations/year (n=160) and >2 exacerbations/year (n=146). Exacerbations were defined as acute/subacute worsening of respiratory symptoms severe enough to warrant oral or intravenous antibiotics. Patient-related factors associated with frequent exacerbations were determined, and clinical outcomes were compared among the three exacerbation groups. Results: Patients with frequent exacerbations were more likely to be female, diabetic and have poorer baseline lung function. Patients with >2 exacerbations/year had an increased risk of experiencing a 5% decline from baseline forced expiratory volume in 1 s (FEV1 ); unadjusted HR 1.47 (95% CI 1.07 to 2.01, p=0.02), adjusted HR 1.55 (95% CI 1.10 to 2.18, p=0.01) compared with patients with <1 exacerbation/year. Patients with >2 exacerbations/year also had an increased risk of lung transplant or death over the 3 year study; unadjusted HR 12.74 (95% CI 3.92 to 41.36, p<0.0001), adjusted HR 4.05 (95% CI 1.15 to 14.28, p=0.03). Conclusions: Patients with CF with frequent exacerbations appear to experience an accelerated decline in lung function, and they have an increased 3 year risk of death or lung transplant.